L’enjeu écologique dans le travail des Land et Reclamation Artists - Adeline Lausson (Cybergeo)
During the sixties, new artistic practices concerned with ecological issues began to appear. In the United States, one could begin to discover monumental artworks consisting of reforestation, depollution, the reintroduction of flora and fauna in deserted areas. Whilst the question reaches a large audience, certain artists are already aware of the way that ecological rehabilitation, and even their own works, could be manipulated. “Will it be a little easier in the future to rip up the landscape for one last shovelful of non-renewable energy source if an artist can be found (cheap, mind you) to transform the devastation into an inspiring and modern work of art? (Robert Morris). If some artists deliberately choose to pursue their researches together with scientists in order to develop unprecedented solutions, others refuse to abandon their scepticism towards a use of art for ecological purposes. From initial projects which are altogether very consensual, they realise artworks which reveal the ambiguity of working in derelict places and denounce the risks of instrumentalising art for political purposes.